Hemin-incorporated nanoflowers as enzyme mimics for colorimetric detection of foodborne pathogenic bacteria. Issue 23 (15th December 2018) - Wang, Kui-Yu; Bu, Sheng-Jun; Ju, Chuan-Jing; Li, Chang-Tian; Li, Zhong-Yi; Han, Ye; Ma, Cheng-You; Wang, Cheng-Yu; Hao, Zhuo; Liu, Wen-Sen; Wan, Jia-Yu
Graphical abstract: Highlights: The nanoflowers could catalyze the ABTS to a colored product. Integrating the functions of both biological recognition and signal amplification. A colorimetric biosensing platform was newly constructed. A useful biocatalyst for bacteria detection and biomedical analysis. Abstract: Rapid, sensitive and point-of-care detection of foodborne pathogenic bacteria is essential for food safety. In this study, we found that hemin-concanavalin A hybrid nanoflowers (HCH nanoflowers), as solid mimic peroxidase, could catalyze oxidation of 2, 2′-azino-bis (3-ethylbenzthiazoline-6-sulfonic acid) diammonium salt (ABTS) in the presence of H2 O2 to a green-colored product. HCH nanoflowers, integrating the essential functions of both biological recognition and signal amplification, meet the requirements of signal labels for colorimetric immunoassay of bacteria. In view of the excellent peroxidase mimetic catalytic activity of HCH nanoflowers, a colorimetric biosensing platform was newly constructed and applied for sensitive detection of foodborne Escherichia coli O157:H7 ( E. coli O157:H7). The corresponding detection limits was as low as 4.1 CFU/mL with wide linear ranges (10 1 –10 6  CFU/mL).